A Critical Survey of Xhosa Lexicography 1772-1989 - Mtuze, P.T. (Lexikos, 1992)
The article critically surveys the development of dictionary making among the Xhosa of Southern Africa. Besides being an analytical commentary on the earlier Xhosa dictionaries, it is also an overdue objective evaluation of The Greater Dictionary of Xhosa currently being compiled at the University of Fort Hare and which promises to be the most definitive Xhosa dictionary this century.